Assistência médica ao parto : estudo comparativo do parto assistido na posição vertical e horizontal - Hyppólito, Silvia Bomfim (1997)
Since a long time, world literature has been demonstrating that medical assistance brought large benefits to complications on deliveries. In the other hand, overused obstetric technologies on normal delivery assistance in hospitals are being questioned. Interventions such as episiotomy, the abuse of oxytocic to shorten the dilatation period and the laying down posture imposed to women during labor are being criticized by a large number of researchers. This study intended to find out if the sitting position to assist the second period of women’s delivery is more appropriate for it is considered physiological. Besides that, no episiotomy has been performed and immediate breastfeeding consequences on blood loss and on the delivery of placenta were observed. The 3.4 minutes difference on favor of the length of time expulsion period to the group of women who delivered on vertical position versus horizontal’s was considered important but not statistic significant (p=0.06). The great majority of mothers has delivered the placenta within the first 25 minutes, regardless they were on the upright (sitting) or neutral (laying down) position. Blood loss was also equivalent on both groups (p=0.52) and breastfeeding did not show any influence on that (p=0.19) and on the time for delivering the placenta (sitting-p=0.08; laying down-p=0.52). The incidence of perineal trauma was 44.1% and 47.0% for women who delivered on vertical and horizontal position, respectively (this incidence was even lower than the 52.3% which is reported on literature). More than 80% of the spontaneous injuries were 1st degree posterior perineal trauma and the rest was just 2nd degree ones, for both groups. It was not evident any advantage of the vertical position over the horizontal’s, during the expulsion period of labor and delivery of placenta. So, mothers could be given the choice in the posture to be assumed during parturition. The absence of oxytocic and episiotomy did not bring any harm to women delivering in any of the two positions. The outcomes do not support medical intervention should be used as routine on normal delivery and for that, those interventions could have a better criteria, avoiding more harm than good and offering a more humanized delivery assistance.